Emotion against reason? Self-control conflict as self-modelling rivalry. - Araya, J. M. (Synthese, 2024)
Divided-mind approaches to the conflict involved in self-control are pervasive. According to an influential version of the divided-mind approach, self-control conflict is a dispute between affective reactions and “cold” cognitive processes. I argue that divided-mind approaches are based on problematic bipartite architectural assumptions. Thus views that understand self-control as “control of the self” might be better suited to account for self-control. I subsequently aim to expand on this kind of view. I suggest that self-control conflict involves a rivalry between narrative self-models aimed at reducing error, analogous to model rivalry in binocular rivalry paradigms. This approach straightforwardly accounts for the sense of conflict that is characteristic of self-control within a unified-mind approach, and among its other explanatory advantages, it directly aligns with current views that account for addiction in terms of maladaptive self-representational processes.